Wdzięczność w kamieniu zapisana. Historia bydgoskiego pomnika Wdzięczności Armii Czerwonej - odsłona II (Kronika Bydgoska, 2010)
The first years after the Second World War were the time of establishing the communist dictatorship in Poland. The communists managed to take control because of the Soviet Union ’s help, so they started to realize Stalin’s plans conseąuently. The communist propaganda manifested itself in many different forms. One of them was building monuments of Gratitude for the Soviet soldiers. But not everybody in Poland was grateful to the Soviet soldiers and the Soviet Union. The problem was that Soviet soldiers died not only for other nations but also for Stalin’s imperialist plans. That was why in 1989, when the communist order collapsed, symbols of the communist propaganda were destroyed, replaced or changed completely. The article depicted the history of the monument of Gratitude for the Soviet soldiers in Bydgoszcz from 1989. The first part of the monumenfs history, which started in 1945, was described by author in “Kronika Bydgoska” XXXI/2009. This article is somehow the continuation of the same problem.